Harnessing marine bacteria for next-gen antibiotics: potent inhibition of S. aureus and Riemerella anatipestifer through in vitro, omics, and chemoinformatics approach with enhanced production of secondary metabolites through zinc sulfate - Hassan, Syed Shams ul; Jin, Huizi (Frontiers in Marine Science, 2025)
The rise of bacterial infections and increasing antibiotic resistance underscores an urgent need for new, effective antimicrobial agents with marine bacteria offering a unique and promising source for novel antibiotic compounds to combat persistent and emerging pathogens. In this research, five compounds were achieved from marine Streptomyces sp., C2-13, and their yield was enhanced with the addition of zinc sulfate at 0.5 mM. All compounds have been evaluated for their antibacterial activity against multiple pathogens, among which good activity was achieved against S. aureus, while potent activity was achieved against Riemerella anatipestifer with its IC50 value at 200 µm and bactericidal effect at 300 µm. Among all compounds, 4 was more active against both pathogens. A transcriptome analysis of active compound 4 showed its antibacterial effect on R. anatipestifer by inhibiting 30S and 50S ribosomal subunits, resistance mechanisms, and gliding motility proteins IX secretion system (T9SS) and interfering with protein translations process, secretion system, defense and resistance mechanisms, ultimately resulting in effective inhibition of normal bacterial growth and its motility. To investigate the anti-bacterial mechanism, all compounds were docked with two enzymes and TLR4 protein for predicting the vaccine construct, and the best docking score was achieved against RMFP with the highest score of -12.9 for compound 4. In silico cloning was carried out to ensure the expression of proteins generated and were cloned using E. coli as a host. The simulation studies have shown that both compound 4–RMFP and TLR4–RMFP complex are stable with the system. To the best of our knowledge, this is the first study investigating marine bacterial metabolites against R. anatipestifer with their anti-bacterial mechanism and enhancing their yield through the addition of zinc sulfate ions.